EVALUATION OF THE EXISTING SIDEWALKS IN DUHOK CITY - N. ABDULSAMAD, QAIDAR; A. MOHAMMED, JAMBALLY; H. ABDULLAH, PIRES (Journal of Duhok University, 2019)
This study investigates the current conditions of the sidewalks in the city of Duhok, northern Kurdistan Region of Iraq, as well as their compatibility with international standard sidewalk regulations. The pedestrian paths in this city are not seen as a preferred transportation mode and therefore, the people find difficulties in walking to the destination and are sometimes obliged to walk in the roads or rather depend on automobiles for traveling to longer destinations. This could be partly attributed to lack, inefficiency or non-attractiveness of the sidewalks in most parts of the city particularly residential areas. Most the sidewalks are generally not conductive to walking in terms of poor design, used improper surface materials, poor surface levelness, increased grading, discontinuity, and the existence of obstacles, such as protruding materials. As a result, the local people do not generally use walking as the preferred mode of travel to destinations; they rather prefer the use of automobiles. On the basis of these facts, this study seeks to present an overview of the structural conditions of the existing sidewalks and to find existing shortcomings compared to the International standards. It also proposes feasible recommendations to provide better sidewalks in order to improve the pedestrian environment and mobility in the city. The study findings indicate that Duhok city needs improved sidewalks, pedestrian facilities to reduce dependence on automobiles and contribute to building a healthy and aesthetic environment.